Multi-Objective Optimization of Rocket-Type Pulse Detonation Engine Nozzles - Alberto Gonzalez-Viana; Francisco Sastre; Elena Martin; Angel Velazquez (Aerospace, 2025)
This numerical study addressed the multi-objective optimization of a rocket-type Pulse Detonation Engine nozzle. The Pulse Detonation Engine consisted of a constant length, constant diameter cylindrical section plus a nozzle that could be either convergent, divergent, or convergent–divergent. The space of five design variables contained: equivalence ratio of the H2-Air mixture, convergent contraction ratio, divergent expansion ratio, dimensionless nozzle length, and convergent to divergent length ratio. The unsteady Euler-type numerical solver was quasi-one-dimensional with variable cross-sectional area. Chemistry was simulated by means of a one-step global reaction. The solver was used to generate three coarse five-dimensional data tensors that contained: specific impulse based on fuel, total impulse, and nozzle surface area, for each configuration. The tensors were decomposed using the High Order singular Value Decomposition technique. The eigenvectors of the decompositions were used to generate continuous descriptions of the data tensors. A genetic algorithm plus a Gradient Method optimization algorithm acted on the densified data tensors. Five different objective functions were considered that involved specific impulse based on fuel, total impulse, and nozzle surface area either separately or in doublets/triplets. The results obtained were discussed, both qualitatively and quantitatively, in terms of the different objective functions. Design guidelines were provided that could be of interest in the growing area of Pulse Detonation Engine engineering applications.